Projections of demand for healthcare in Ireland, 2015-2030: First report from the Hippocrates Model - Wren, Maev-Ann; Keegan, Conor; Walsh, Brendan; Bergin, Adele; Eighan, James; Brick, Aoife (ESRI)
This report provides annual projections of demand for public and private health and social care services in Ireland for the years 2015-2030. These projections are based on new ESRI projections for population growth, the first projections to be published b
PUBLISHED